Theme: Topic or Discourse Framework? - María A. Gómez González (Miscelánea: A Journal of English and American Studies, 1996)
Halliday's notion of (Topical) Theme has been questioned by Huddleston and Downing, inter alia. Their criticism focuses on the idea that the first element in an English clause, Halliday’s (Topical) Theme, does not always identify “what the clause is about.” This debate rests on three different interpretations of thematic/topical “aboutness.” Whereas Halliday understands “aboutness” in a relational sense, Huddleston and Downing support an interactive referential and a contextual referential interpretation, respectively. Section 1 outlines the points involved in three accounts. Section 2 expands Downing's and Huddleston's views, which section 3 tries to reconcile with a relational interpretation of the ‘aboutness’ feature of Halliday’s (Topical) Theme. Section 4 comprises the main conclusion drawn therefrom, namely that Halliday’s (Topical) Theme and Huddleston’s and Downing’s Topic invoke different functions, which may, but need not, be conflated or “mapped” onto one another.